Influencia de los factores tecnológico, organizacional y ambiental en la adopción de redes sociales en pymes importadoras del sector droguería - Abal Limache, Diana Paola (2022)
In today's globalized world, innovation and the implementation of new technologies in business have become an important factor for the development of companies, especially SMEs, which use of all their resources with the objective of generating value in terms of productivity to continue growing. In this sense, social networks, being a tool, in a certain way without cost, is often used to communicate with customers. The reason why they decide to use certain technological tools may vary according to the characteristics of each SME. The purpose of this study is to explore the factors that influence the adoption of social networks and explain the relationship of these factors with the adoption of social networks in importing SMEs in the drugstore sector. An existing conceptual model is proposed that explains the adoption of new technologies (the TOE – Technological-Organizational-Environmental model) to achieve the objective of the research, for which a survey was applied to 59 importing SMEs of the drugstore sector in Peru. As a result of the study, it was found that the technological factor significantly influences the adoption of social networks in importing SMEs from the drugstore sector. Likewise, the moderating role of organizational and environmental factors are proven, but no relationship is found with the adoption of social networks. The results of the present study and its findings represent a contribution for future research on this elementary topic, as well as for organizations that are seeking to adopt social media networks.